2018
DOI: 10.1038/s41467-018-05710-7
|View full text |Cite
|
Sign up to set email alerts
|

The Arp8 and Arp4 module acts as a DNA sensor controlling INO80 chromatin remodeling

Abstract: Nuclear actin and actin-related proteins (Arps) are key components of chromatin remodeling and modifying complexes. Although Arps are essential for the functions of chromatin remodelers, their specific roles and mechanisms are unclear. Here we define the nucleosome binding interfaces and functions of the evolutionarily conserved Arps in the yeast INO80 chromatin remodeling complex. We show that the N-terminus of Arp8, C-terminus of Arp4 and the HSA domain of Ino80 bind extranucleosomal DNA 37–51 base pairs fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
65
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(72 citation statements)
references
References 37 publications
7
65
0
Order By: Relevance
“…To effect sliding, INO80 requires at least 40 -50 bp of free extranucleosomal DNA ahead of the nucleosome 19,20 . The region around 40 -50 bp ahead of the sliding nucleosome's edge is enganged by the Arp8 module of INO80 [21][22][23] , and disrupting the module's DNA binding via mutation abolishes sliding and reduces +1 positioning genome-wide 23 . Intriguingly, we found that the region of rigid DNA also starts ~43 bp upstream of the edge of the +1 nucleosome (Fig.…”
Section: Chromatin Remodelers Sense Dna Mechanicsmentioning
confidence: 99%
“…To effect sliding, INO80 requires at least 40 -50 bp of free extranucleosomal DNA ahead of the nucleosome 19,20 . The region around 40 -50 bp ahead of the sliding nucleosome's edge is enganged by the Arp8 module of INO80 [21][22][23] , and disrupting the module's DNA binding via mutation abolishes sliding and reduces +1 positioning genome-wide 23 . Intriguingly, we found that the region of rigid DNA also starts ~43 bp upstream of the edge of the +1 nucleosome (Fig.…”
Section: Chromatin Remodelers Sense Dna Mechanicsmentioning
confidence: 99%
“…The affinity of the protein to DNA especially with the Hs.con sequences is low; however, we observed that compared to the cloned protein, the nuclear extracts showed higher affinity to DNA The structure and interaction of the sub-complexes of the canonical INO80 complex has been analysed; it was shown that Ino80 (via the HSA domain), Arp8 (via N-terminus) and Arp4 (via C-terminus) interact with the extranucleosomal DNA in yeast [39]. The HSA domain of Ino80 along with the spacer (protrusion region 2) was demonstrated to bind to specific nucleotides at entry DNA (nts -110/-111 and -124) [39]. In another report, the crystal structure of the Arp8 module of yeast INO80 established that the HSA domain provides a binding platform for extranucleosomal entry DNA for bringing about nucleosome sliding in yeast Ino80 [38].…”
Section: Discussionmentioning
confidence: 89%
“…Notably, the functional domains (ATP-and nucleotide-binding sites), which are the most crucial for ACTR8 function, are well preserved in TV2-TV6. According to a previous study, the N-terminal region of ACTR8 is critical for functional activity and N-terminal deletions have deleterious effects on the expressed protein, whereas deletions in the C-terminal region did not have such effects [29][30][31].…”
Section: Protein Structure Analysis Of Various Actr8 Gene Transcriptsmentioning
confidence: 94%